KEBIJAKAN EFISIENSI BELANJA NEGARA DAMPAKNYA PADA FUNGSI PERBANKAN PUBLIK DAN PEMBIAYAAN EKONOMI - Hendrizoni Hendrizoni; Ridwan Putra; Hilda Elsa Sari (Ensiklopedia of Journal, 2026)
State spending efficiency policy is a crucial component of a country's financial management policy. Its goal is to improve the quality of public spending and maintain economic stability. This study examines the legal impact of state spending efficiency policy on the role of state-owned banks in financing the national economy. This study uses a normative legal method, examining laws and regulations and their concepts. The results indicate that state spending efficiency policy impacts state-owned banks. These banks function not only as commercial businesses but also as instruments of the state's fiscal policy. From a legal perspective, state spending efficiency raises several questions about how this policy impacts the state's banking and financial system. This raises the need for legal certainty and regulatory harmonization between state financial law and banking law to ensure that the implementation of public banking's intermediation function remains in line with the principles of prudence and accountability. Therefore, a responsive and integrated legal policy is needed to ensure that state spending efficiency does not undermine the strategic role of public banks in financing the national economy.Keywords: state spending efficiency, fiscal policy, public banking, economic financing, legal implications